2004
DOI: 10.1016/s1525-1578(10)60495-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MGB1 as a Marker in the Differential Diagnosis of Lung Tumors in Patients with a History of Breast Cancer by Analysis of Publicly Available SAGE Data

Abstract: The risk of developing second primary cancers is increased in patients with breast cancer. The lung is one of the major target organs, and therefore a differential diagnosis between primary and metastatic cancers is required for the treatment of lung tumors in patients with a history of breast cancer. However, biopsy specimens frequently result in small, fragmented tissues containing only a few, degenerated cancer cells. We attempted to find a useful marker for differential diagnosis, using the online SAGE dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…The result was consistent with mRNA expression patterns described previously. 7 As endometrial and salivary gland cancers were reported to express MGB1 mRNA, 7,15 25 additional endometrial and salivary gland tumors were examined. MGB1 was positive in two of 14 endometrial tumors (14%) and in six of 11 salivary gland tumors (55%; three of four pleomorphic adenomas, one of four adenoid cystic carcinomas, one of one mucoepidermoid carcinoma and one of two salivary duct carcinomas).…”
Section: Mgb1 Expression Specific For Breast Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was consistent with mRNA expression patterns described previously. 7 As endometrial and salivary gland cancers were reported to express MGB1 mRNA, 7,15 25 additional endometrial and salivary gland tumors were examined. MGB1 was positive in two of 14 endometrial tumors (14%) and in six of 11 salivary gland tumors (55%; three of four pleomorphic adenomas, one of four adenoid cystic carcinomas, one of one mucoepidermoid carcinoma and one of two salivary duct carcinomas).…”
Section: Mgb1 Expression Specific For Breast Cancersmentioning
confidence: 99%
“…5,6 Using the SAGE database of the NCBI, we independently found that this molecule is a differential marker between primary lung cancer and metastatic cancer from the breast. 7 The RNA-based assay for MGB1 adequately distinguished breast cancer metastasis from primary lung cancer. Recently, an anti-MGB1 antibody, which can be applied to formalin-fixed, paraffinembedded sections, was made commercially available.…”
mentioning
confidence: 99%
“…In addition to using the estrogen receptor (ER) antibody, which is known as a differential marker for the discrimination of metastatic breast cancer, creation of a panel of antibodies was remarkably useful in obtaining definitive diagnosis [21,22]. Further, mammaglobin 1 (MGB1) was shown to be specifically expressed in breast cancer, and therefore suggested as a useful molecular marker for differentiation of metastatic breast cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic, chromosomal loss of heterozygosity and comparative genomic hybridization analyses have revealed multiple chromosomal as well as genetic changes in lung cancer. 2,3 In the past decade, gene expression-based studies, such as serial analysis of gene expression (SAGE) and cDNA microarray analyses, have revealed the gene expression signatures of lung cancer [4][5][6][7][8][9][10][11] and provided lung cancer subclassification 12 and prognosis. 10,13 Using the SAGE, we have showed that 115 highly differentially expressed genes were able to distinguish the neoplastic state as well as the tissue type of the lung tumors.…”
mentioning
confidence: 99%